Features of Metrological Support at JSC Gazprom in the Conditions of Digitalization - Brusakova, Irina A. (2019 XXII International Conference on Soft Computing and Measurements (SCM), 2019)
The paper presents the main features of the analysis of business processes of metrological support of the enterprises of JSC Gazprom in the conditions of digital transformation and the technological SAP NW HANA platform. The paper shows the main stages of drafting the metrological passport of the enterprise in the conditions of technological processes automation. The paper proposes novel mechanisms for business planning of metrological services and gives the stages of the analysis of measuring information.